Analisis Kesesuaian Antara Penerapan Akuntansi Aset Tetap dengan PSAP No. 07 pada Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat - Naufal Farhan Windhuaji; Nunung Aini Rahmah (Transpublika Publisher, 2025)
The purpose of this research was to assess how well fixed asset accounting was being implemented in the Bina Marga and Spatial Planning Office in the West Java Province, following PSAP No. 07 guidelines on Fixed Asset Accounting Standards. The researchers used a descriptive qualitative method to gather information, which included observations, interviews, and reviewing documents. The data used comes from various sources, including the results of interviews and documents such as the Financial Statements of the Asset Balance Sheet for the period 2023-2024, reports on ownership of regional goods in 2024, inventory lists of regional goods in 2024, and related legal regulations. The aim of this study is to gain fresh insights into how fixed asset accounting is carried out in line with PSAP No. 07. The findings suggest that the fixed asset accounting practices at the Bina Marga and Spatial Planning Office in West Java Province are in line with the guidelines set out in PSAP No. 07, covering aspects such as classification, recognition, measurement, post-acquisition expenditure, depreciation, disposal, and disclosure of fixed assets.